2021
DOI: 10.3390/ijms221910462
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Response to Hepatitis B Virus Infection and Potential of TLR Agonists as Immunomodulators for Treating Chronic Hepatitis B: An Overview

Abstract: Chronic hepatitis B virus (HBV) infection remains a major global health problem. The immunopathology of the disease, especially the interplay between HBV and host innate immunity, is poorly understood. Moreover, inconsistent literature on HBV and host innate immunity has led to controversies. However, recently, there has been an increase in the number of studies that have highlighted the link between innate immune responses, including Toll-like receptors (TLRs), and chronic HBV infection. TLRs are the key sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 136 publications
(156 reference statements)
0
41
0
Order By: Relevance
“…TLR3 also recruits TRAF6 to phosphorylate TAK1. TAK1 sensitizes AP-1 via the activation of the MAPK pathway and activate NF-kB via the IKK-IkB complex to modulate the inflammatory reaction (33)(34)(35)(36)(37)(38).…”
Section: Effect Of Hbx On Tlr-mediated Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…TLR3 also recruits TRAF6 to phosphorylate TAK1. TAK1 sensitizes AP-1 via the activation of the MAPK pathway and activate NF-kB via the IKK-IkB complex to modulate the inflammatory reaction (33)(34)(35)(36)(37)(38).…”
Section: Effect Of Hbx On Tlr-mediated Signaling Pathwaysmentioning
confidence: 99%
“…Accumulating data shows that initiating the host TLR response is a new therapeutic strategy for HBV infection ( 36 , 37 ). Several studies have demonstrated that the stimulation of TLR2-5, TLR7, and TLR9 with their specific ligands can inhibit HBV replication in the cell and animal models ( 38 ). Furthermore, the potential of TLR agonists, including GS-9620, RO7020531, JNJ-64794964 (TLR7 agonists), GS-9688 (TLR8 agonist), and AIC649 (TLR9 agonist), has been investigated in clinical trials at different stages ( 38 , 39 ).…”
Section: Effect Of Hbx On Tlr-mediated Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing interest in the use of TLR agonists as immunomodulators for the treatment of inflammation, cancer, infection, allergy, and autoimmunity. The use of TLR agonists to modify immunotherapeutic effects also appears promising [93][94][95][96][97][98][99]. Moreover, TLRs, which are considered as important triggering molecules of trained immunity, trigger a long-term boosting of innate immune responses [100].…”
Section: Tlr Agonists As Covid-19 Vaccine Adjuvantsmentioning
confidence: 99%